2012
DOI: 10.1200/jco.2011.37.2482
|View full text |Cite
|
Sign up to set email alerts
|

Clinically Used Breast Cancer Markers Such As Estrogen Receptor, Progesterone Receptor, and Human Epidermal Growth Factor Receptor 2 Are Unstable Throughout Tumor Progression

Abstract: PURPOSE To investigate whether hormonal receptors and human epidermal growth factor receptor 2 (HER2) change throughout tumor progression, because this may alter patient management. PATIENTS AND METHODS The study cohort included female patients with breast cancer in the Stockholm health care region who relapsed from January 1, 1997, to December 31, 2007. Either biochemical or immunohistochemical (IHC)/immunocytochemical (ICC) methods were used to determine estrogen receptor (ER), progesterone receptor (PR), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
334
2
8

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 434 publications
(371 citation statements)
references
References 30 publications
27
334
2
8
Order By: Relevance
“…There has been a general belief that this is also a natural cause of breast cancer progression in humans. Evidence shows that this is not the case; the majority of ER þ primary breast cancers maintain ER expression in metastases, and nearly a third gain ER expression in metastatic lesions (37). This underscores the importance of understanding estrogendependent mechanisms of breast cancer progression as a prerequisite for finding novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 90%
“…There has been a general belief that this is also a natural cause of breast cancer progression in humans. Evidence shows that this is not the case; the majority of ER þ primary breast cancers maintain ER expression in metastases, and nearly a third gain ER expression in metastatic lesions (37). This underscores the importance of understanding estrogendependent mechanisms of breast cancer progression as a prerequisite for finding novel therapeutic targets.…”
Section: Discussionmentioning
confidence: 90%
“…The prognostic impact of discordance between expression of receptors in the primary and metastatic tumors is not clear. A retrospective study by Lindström et al showed that discordant cases have worse survival [36], whereas a prospective trial by Amir et al failed to demonstrate adverse effects on clinical outcome [37]. In our study, 4 of 18 patients with an HR-positive primary tumor changed to HR-negative status in the BM, whereas 7 of 17 patients with an HR-negative primary tumor changed to HRpositive status in the BM; loss or gain of HR expression in the brain metastases appears to have no significant effect on survival after diagnosis of BCBM.…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that patients with ER (−) and HER-2 (+) breast cancer have poorer prognoses than patients with ER (+) and HER-2 (−) breast cancer [5,34,35]. Higashi et al [36] reported that RI can predict the hexokinase-II expression and suggested possible prognostic values of RI.…”
Section: Discussionmentioning
confidence: 99%